2022
DOI: 10.31234/osf.io/4bgkd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gamified Inoculation Interventions Do Not Improve Discrimination Between True and Fake News: Reanalyzing Existing Research With Receiver Operating Characteristic Analysis

Abstract: Gamified psychological interventions designed to improve detection of online misinformation are becoming increasingly prevalent. Two of the most notable interventions of this kind are Bad News and Go Viral!. To assess their efficacy, prior research has typically used pre-post designs in which participants rated the reliability or manipulativeness of true and fake news items before and after playing these games, while most of the time also including a control group who played an irrelevant game (i.e., Tetris) o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Although more recent articles have addressed some of these problems, there is arguably still scope for improvement. Furthermore, a graphical analysis of the results of these prior investigations (Figure 1) suggests that when people are not certain about the veracity of news items to begin with, Bad News may simply make them generally more skeptical of news items, regardless of whether they are true or fake (see Modirrousta-Galian & Higham, 2022, for further discussion on this issue). Reduced belief in truth (e.g., that COVID-19 booster vaccines are important) can sometimes be more damaging than increased belief in falsehoods (e.g., that 5G towers cause COVID-19).…”
Section: Inductive Learningmentioning
confidence: 99%
“…Although more recent articles have addressed some of these problems, there is arguably still scope for improvement. Furthermore, a graphical analysis of the results of these prior investigations (Figure 1) suggests that when people are not certain about the veracity of news items to begin with, Bad News may simply make them generally more skeptical of news items, regardless of whether they are true or fake (see Modirrousta-Galian & Higham, 2022, for further discussion on this issue). Reduced belief in truth (e.g., that COVID-19 booster vaccines are important) can sometimes be more damaging than increased belief in falsehoods (e.g., that 5G towers cause COVID-19).…”
Section: Inductive Learningmentioning
confidence: 99%
“…Although the effectiveness of news media literacy interventions and pre-bunking techniques requires more empirical research, our findings suggest that it is important to look at the discernment between factually accurate information and mis-or disinformation to measure the effectiveness of interventions (see also e.g., Modirrousta-Galian & Higham, 2022). Hence, under some conditions, exposure to a media literacy intervention can lower the credibility of information irrespective of its veracity.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, to comprehensively measure the effectiveness of warning labels and media literacy interventions, it is important to distinguish between the acceptance of misinformed claims and factually accurate information. Considering that experimental research found that being exposed to a warning label before seeing factually accurate information can also lower the trustworthiness of true information (Hameleers, 2022;Modirrousta-Galian & Higham, 2022), this article explores how the presentation of a warning label combined with a media literacy intervention placed before factually accurate information and mis-or disinformation influences the rating of both types of information.…”
Section: Mis-and Disinformation As Informational Perceptual and Discu...mentioning
confidence: 99%
“…These effects were asymmetrical, with a larger suppression effect estimated for misinformation than for legitimate information, suggesting some improvement in ability to discriminate among inoculated participants. Future experiments should aim to further explore the mechanisms by which inoculation works, as there is recent evidence that it may catalyse more conservative engagement with posts rather than substantially improving discernment (Modirrousta-Galian & Higham, 2022). If this is indeed the case, social media platforms, policymakers and regulators will be forced to weigh the benefits of decreasing the spread of misinformation via inoculation against the social costs associated with a reduction in the dissemination of legitimate information.…”
Section: Discussionmentioning
confidence: 99%